The Relationship Between the Sandwich Generation and Early Childhood Moral Development - Jauharin Insiyah; Maria Qoriah; Viena Wanidha Andriani (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to empirically examine the relationship between the role of the sandwich generation and the moral development of early childhood at RA Tunas Cendekia Glenmore. The sandwich generation refers to a group of individuals who experience dual financial and emotional responsibilities, as they are required to care for their aging parents while simultaneously raising children who remain dependent on them. This dual-role strain frequently triggers psychological stress, which has the potential to reduce parental warmth and consistency in parenting practices, thereby influencing children's moral development. Employing a quantitative correlational research design, data were collected from a purposive sample of 60 parents at RA Tunas Cendekia using purposive sampling techniques. Data collection instruments consisted of closed-ended questionnaires based on a Likert scale, and the data were analyzed using the Pearson Product-Moment Correlation Coefficient. Statistical analysis yielded a Pearson correlation coefficient of 0.43, indicating a moderate or moderately strong correlation (0.40–0.70) based on Sugiyono's interpretation criteria. These statistical findings demonstrate a significant relationship between the level of parental dual-role strain within sandwich-generation families and the moral development of early childhood. The study concludes that interventions in the form of effective parenting strategies and strong social support systems are essential for sandwich-generation families to maintain the quality of children's moral development during the golden age.